2018
DOI: 10.1039/c8cp03725f
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic fragmentation of H2O+ and isotopomers. Wave packet propagation using ab initio wavefunctions

Abstract: The nonadiabatic fragmentation of excited water cations (and isotopomers) is studied by propagating wave packets on ab initio potential energy surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 41 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…H 2 O + (Ã) has a dissociation energy of about 4.2 eV, which also rules out its contribution to fragmentation at 4 eV and below. On the other hand, H 2 O + (B), which only supports two bound vibrational levels, can easily dissociate above 0.3 eV via a conical intersection that populates statesà andX ; for energies above 2.7 eV, dissociation directly on theB PES is also possible [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…H 2 O + (Ã) has a dissociation energy of about 4.2 eV, which also rules out its contribution to fragmentation at 4 eV and below. On the other hand, H 2 O + (B), which only supports two bound vibrational levels, can easily dissociate above 0.3 eV via a conical intersection that populates statesà andX ; for energies above 2.7 eV, dissociation directly on theB PES is also possible [17].…”
Section: Discussionmentioning
confidence: 99%
“…The study of the PESs corresponding to the three resonances identified in the previous section has been carried out in the grid of points (set of geometries) used in Suárez et al [17]. This grid is defined in the Jacobi coordinates {R, r, θ} illustrated in Fig.…”
Section: B Resonance Parameters As a Function Of Cation Geometrymentioning
confidence: 99%
See 3 more Smart Citations